The Implementation of Blended Learning Model on Motivation and Students’ Learning Achievement - Rahman, Zeinor; Rijanto, Tri; Basuki, Ismet; Sumbawati, Meini Sondang (Universitas Malikussaleh, 2020)
This study aims to determine differences in student motivation and learning achievement in KKPI subjects between students who use the face-to-face learning model and students who use blended learning models, increased motivation and student achievement in KKPI subjects due to the application of the blended model learning, and the interaction of the influence of the application of learning models and motivation on KKPI student learning achievement at SMK 1 Kamal Bangkalan. This quasi-experimental study uses two groups, namely the experimental group using the blended learning model and the control group using the face-to-face learning model. The study population was students of class XI SMKN 1 Kamal Bangkalan. The research sample consisted of 57 students divided into 30 students in the control group and 27 students in the experimental group. Data collection using questionnaires and multiple choice test questions. The results showed that there were significant differences between motivation and student achievement using the blended learning model and students using the face-to-face learning model, there was a significant increase in student motivation and learning achievement due to the application of the blended learning model, and there was no interaction of influence the application of learning models and motivation to student learning achievement.